(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Over the last three decades, there has been increasing global concern over the public health impacts attributed to direct and indirect environmental pollution, in particular, the global burden of disease. The World Health Organization estimates that, about a quarter of the diseases facing mankind today occur due to prolonged exposure to environmental pollution; the health of 200 million people in lower-income countries is at risk from toxins such as lead and copper or mercury, more than from AIDS, tuberculosis and malaria combined and that, nearly a quarter of deaths in developing countries including Nigeria and Ghana, are linked to pollution. The purpose of the study was to investigate the effects of the ingestion of large dose of copper on the structural stability of collagen molecules, as well as reveal age-dependent differences in the phenomena. The content of de novo synthesized collagen was determined by hydroxyproline concentration using Stegmann-Staeder’s method as modified by Utevskaya and Persky; the nature of intra- and inter-molecular covalent cross-links in collagen matrix was estimated by electrophoretic separation of products of partial thermal denaturation of collagen in polyacrylamide gel. There was intensification of synthesis over degradation in young rats, and that administration of copper led to a decrease in collagen solubility. Effects of copper on the structural stability of collagen appeared mostly in young rats.